Filling the gap : Nietzsche's account of authenticity as a supplementary ideal - Baker, Michaela Christie (Rhodes University, Faculty of Humanities, Department of Philosophy, 2004)
This thesis examines the ideal of authenticity: why we might want or need such an ideal, what such an ideal would look like, and what mechanisms we would need to ensure the successful operation of such an ideal. The thesis has three main parts. The first part of the thesis aims at motivating the need to look to authenticity as a supplementary ideal to normative moral theory. I do this by drawing a distinction between ethics and morality and arguing that there are important aspects of our lives (such as our relations to ourselves) our beliefs and projects) about which normative moral theory fails to give us guidance and about which an ethical ideal, namely that of authenticity, can provide us with the requisite guidance. The second part of the thesis elucidates Nietzsche's view of authenticity as eternal return. I argue that eternal return consists in holding a particular attitude to one's life - one's past, present and future. I then demonstrate that what is fundamental to successfully living authentically in accordance with eternal return is a rigorous search for self-knowledge. In the third part of the thesis I argue that, in order to achieve the self-knowledge necessary to being a successful authentic agent, one must acquire it through a process of dialogue with other agents. I give a model of self-knowledge as a dialogic encounter that provides two important mechanisms whereby such self-knowledge can be gained.
Keywords: Nietzsche, Friedrich Wilhelm, 1844-1900 -- Ethics; Authenticity (Philosophy); Ethics, Modern; Normativity (Ethics); Self-knowledge, Theory of